The influence of selected socio-demographic variables on symptoms occurring during the menopause - Makara-Studzińska, Marta; Kryś-Noszczyką, Karolina; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction: It is considered that the lifestyle conditioned by socio-demographic or socio-economic factors determines the health condition of people to the greatest extent. The aim of this study is to evaluate the influence of selected socio-demographic factors on the kinds of symptoms occurring during menopause. Material and methods : The study group consisted of 210 women aged 45 to 65, not using hormone replacement therapy, staying at healthcare centers for rehabilitation treatment. The study was carried out in 2013-2014 in the Silesian, Podlaskie and Lesser Poland voivodeships. The set of tools consisted of the authors’ own survey questionnaire and the Menopause Rating Scale (MRS). Results : The most commonly occurring symptom in the group of studied women was a depressive mood, from the group of psychological symptoms, followed by physical and mental fatigue, and discomfort connected with muscle and joint pain. The greatest intensity of symptoms was observed in the group of women with the lowest level of education, reporting an average or bad material situation, and unemployed women. Conclusions : An alarmingly high number of reported psychological symptoms in the group of menopausal women was observed, and in particular among the group of low socio-economic status. Career seems to be a factor reducing the risk of occurrence of psychological symptoms. There is an urgent need for health promotion and prophylaxis in the group of menopausal women, and in many cases for implementation of specialist psychological assistance.